The Direction of KH. Ali Yafie's Progressive Islamic Paradigm: An Analysis of the Dialogue's Intersection Between Text and Reality - Syihabuddin, Muhammad; Mubaraq, Zulfi; Mustofa, M. Lutfi (FIKRAH, 2024)
Progressive Islamic KH. Ali Yafie thought’s, who is moderate and contextual, has significance and relevance in facing the challenges of the times in Indonesia. This article aims to understand the direction of Ali Yafie's thinking regarding progressive Islam, in interpreting texts over context, and the production of social fiqh. The method used is a qualitative method based on literature review, with data collection through literature review, especially the main work of KH. Ali Yafie and relevant articles as secondary sources. The analysis technique applied is content analysis. The results of the study show three main things: first, the genealogical of KH's progressive thinking. Ali Yafie in Indonesia was influenced by Indonesia's socio-political developments and the needs of Muslims. Second, the interpretation method of KH. Ali Yafie emphasizes the synergy between texts and social contexts, by presenting interpretations that emphasize the balance of understanding religious texts and social reality. Third, social fiqh in the thought of KH. Ali Yafie aims to achieve social justice through a progressive approach by using fiqh as an instrument to achieve social justice, especially through wealth redistribution, empowerment of marginalized groups, and political participation of Muslims. This article contributes to the understanding of the flexibility of Islam as a religion that is rahmatan lil 'alamin